Type 1 secretion system and effectors in Rickettsiales - Bui, Duc-Cuong; Luo, Tian; McBride, Jere W. (Frontiers in Cellular and Infection Microbiology, 2023)
Obligate intracellular bacteria in the order Rickettsiales are transmitted by arthropod vectors and cause life-threatening infections in humans and animals. While both type 1 and type 4 secretion systems (T1SS and T4SS) have been identified in this group, the most extensive studies of Rickettsiales T1SS and associated effectors have been performed in Ehrlichia. These studies have uncovered important roles for the T1SS effectors in pathobiology and immunity. To evade innate immune responses and promote intracellular survival, Ehrlichia and other related obligate pathogens secrete multiple T1SS effectors which interact with a diverse network of host targets associated with essential cellular processes. T1SS effectors have multiple functional activities during infection including acting as nucleomodulins and ligand mimetics that activate evolutionarily conserved cellular signaling pathways. In Ehrlichia, an array of newly defined major immunoreactive proteins have been identified that are predicted as T1SS substrates and have conformation-dependent antibody epitopes. These findings highlight the underappreciated and largely uncharacterized roles of T1SS effector proteins in pathobiology and immunity. This review summarizes current knowledge regarding roles of T1SS effectors in Rickettsiales members during infection and explores newly identified immunoreactive proteins as potential T1SS substrates and targets of a protective host immune response.